A Book Review of John Dewey’s Democracy and Education: An Introduction to the Philosophy of Education - Kara Flanagan (Canadian Journal for New Scholars in Education)
Over one hundred years after the publication of Democracy and Education: An Introduction to the Philosophy of Education, John Dewey’s (1916) teachings continue to exhibit a strong influence on educational studies. The universal, yet practical, messages he provides offer a framework for students to adapt to changing times. In the philosophy of John Dewey, it is experience that genuinely shapes and provides meaning to my practice in education in the field of acting. This book review will discuss Dewey's main themes and respond to his philosophy in a twenty-first century context of education relating my personal experiences studying acting in North America.